Low-cost closed-loop control of a 3D printer gantry. Issue 5 (17th August 2015) - Weiss, Benjamin; Storti, Duane W.; Ganter, Mark A.
Abstract : Purpose: – The purpose of this paper is to explore the improvements in speed and precision achievable using straightforward closed-loop control for the gantry motion in additive manufacturing machines. The authors designed and built an economically viable demonstration system to quantify the performance improvement. Design/methodology/approach: – The authors develop and evaluate a low-cost closed-loop controller for the X and Y axes of an entry-level three-dimensional (3D) printer. The system developed captures and compensates for the dynamics of the motor and the belt-driven stage and detects mechanical errors, such as skipped motor steps. Findings: – The system produces path-following precision improvements of 40 and 75 per cent for two different sample trajectories. Correcting for skipped steps increases reliability and allows for more aggressive tuning of motion parameters; time savings of up to 25 per cent are seen by doubling acceleration rate. Research limitations/implications: – The system presented provides an appropriate platform for further investigation into more complex, application-specific controllers and inclusion of more details of the printer dynamics that could produce still greater improvements in speed and accuracy. Practical implications: – The performance, low cost (40 USD/axis) and applicability to the majority of sub-2000USD 3D printer designs make this work of practical significance. Originality/value: – The CNC machining industry has for many years used similar approaches, but application to 3D printers has not been explored in the literature. This paper demonstrates the value of even a simple controller applicable to almost any 3D printer, while maintaining cost-effectiveness of the solution in a competitive market.